(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Background: This study compares performance anxiety and aggression between female swimmers and female para-swimmers. It aims to identify significant differences and provide recommendations for enhanced psychological support for both groups. Objective: To compare and analyse performance anxiety and aggression levels between para and able-bodied swimmers, identify key contributing factors, and develop recommendations for improved psychological support and coping strategies for both groups. Method: This study involved a total of 50 national-level subjects, consisting of 25 female swimmers and 25 female para-swimmers, to identify previously unknown psychological drawbacks. All participants were aged between 18 and 30 years. Tests were administered to assess psychological variables including Aggression and Competitive State Anxiety as well as influencing factors in their sports careers. Result: The analysis revealed that female swimmers had significantly higher levels of aggression (M = 80.04, SD = 14.72) and competitive state anxiety (M = 19.35, SD = 3.01) compared to female para-swimmers, who had lower scores in both areas (aggression: M = 72.04, SD = 13.77; anxiety: M = 17.08, SD = 5.91). T-tests showed significant differences in aggression (t = 2.02, p = 0.048) and anxiety (t = 2.99, p = 0.004) between the two groups, indicating that female swimmers experience higher levels of both psychological variables than female para-swimmers. Conclusion: Female swimmers show significantly higher levels of aggression and competitive state anxiety compared to female para-swimmers. These findings highlight the need for targeted psychological support to address these elevated levels and improve overall athlete well-being and performance.